Like Light, Like Music - Austin, Lana K. W. (Book collections on Project MUSE., 2020)
"Emme McLean never imagined that in 1999 she would be living out the lyrics of the ancient murder ballads she grew up singing. But now she is back in Red River, Kentucky, using her skills as a journalist to prove her cousin did not kill her husband and to find out what is terrifying the town after many of its women went half-mad on the same night"--